Sizes and shapes of simulated amorphous cis- and trans-1, 4-polybutadiene. (7th April 2015) - Kar, Suvrajyoti; Greenfield, Michael L.
Abstract: Controlling loss modulus can decrease tire rolling resistance. Deformation forces in elastomers depend on chain conformation. As a first step toward screening chemical effects on these, isolated single cis- and trans-1, 4-polybutadiene chains of uncorrelated random conformations under unperturbed conditions are generated using Flory's Rotational Isomeric State approach, with discrete rotational states defined by Mark, Abe, and Flory. Averages and distribution of squared end-to-end distance, radius of gyration, and shape parameters are studied for chains ranging from 15 to 120 repeat units at 343 K and for the 50-unit chain at temperatures of 275 K–400 K. The calculated characteristic ratios are in good agreement with experimental and prior computed values. Only small absolute changes in chain size probability densities with temperature are found. A larger relative increase in probability density of unlikely larger chains and a smaller relative decrease in probability density of more likely smaller chains result in increased average chain size and characteristic ratios with increasing temperature. Within subdivisions of the size distribution, larger chains show an increase in characteristic ratio with temperature, while smaller and medium size chains show little change with temperature. This previously unreported effect is stronger for trans than for cis chains. Eigenvalues of the radius of gyration matrix quantify chain shapes along principal directions. Averaged shape measures differ between cis and trans chains, and most shape changes arise along the longest principal direction. Joint correlations between chain size and shape show they are mutually dependent. Graphical abstract: